Insights into the Use of Eco-Friendly Synergists in Resistance Management of Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) - Rana Muhammad Kaleem Ullah; Ayhan Gökçe; Allah Bakhsh; Muhammad Salim; Hai Yan Wu; Muhammad Nadir Naqqash (Insects, 2022)
The Colorado potato beetle (CPB), Leptinotarsa decemlineata (Say), is the most notorious insect pest of potato globally. Injudicious use of insecticides for management of this pest has resulted in resistance to all major groups of insecticides along with many human, animal health, and environmental concerns. Additionally, the input cost of insecticide development/discovery is markedly increasing because each year thousands of chemicals are produced and tested for their insecticidal properties, requiring billions of dollars. For the management of resistance in insect pests, synergists can play a pivotal role by reducing the application dose of most insecticides. These eco-friendly synergists can be classified into two types: plant-based synergists and RNAi-based synergists. The use of plant-based and RNAi-based synergists in resistance management of insect pests can give promising results with lesser environmental side effects. This review summarizes the resistance status of CPB and discusses the potential advantage of plant-based and RNAi-based synergists for CPB resistance management. It will motivate researchers to further investigate the techniques of using plant- and RNAi-based synergists in combination with insecticides.